All Optical UWB-DWDM for Medical Applications Based on Optical Phase Conjugation Technique - Ali Hayder Abdul Kareem (Journal of Global Pharma Technology, 2017)
In this paper, optical phase conjugation (OPC) devices are used along the optical link as a new method for improving the performance of wireless medical communications using all optical UWB signal. A 50 GHz spaced two-channel dense wavelength division multiplexing (DWDM) communication system is considered using 360 km single mode fiber (SMF) link with two pumps. Simulation results are compared with the case of without using compensation technique showing better performance in terms of achievable Q-factor, BER performance, and the total length of transmission link.Keywords: All optical UWB, DWDM technique, Optical Phase Conjugation (OPC), Wireless medical communication.